EXAMINING RELATIONSHIPS AMONG CIPP COMPONENTS IN SENIOR HIGH SCHOOL ENGLISH CLASSES UNDER THE MERDEKA CURRICULUM - Eva Meidi Kulsum; Revi Nur Ridwan; Ayang Winda Sri Widianingsih; Rina Mutiarawati; Astried Intan Aprilliana (University of Kuningan, 2026)
With the establishment of the Merdeka Curriculum, education in Indonesia is stepping into a new chapter, aiming to place students at the center of the learning process, encourage differentiated instruction, and strengthen essential 21st-century skills. Despite its promising vision, most existing studies focus mainly on descriptive accounts of policy implementation, offering little empirical evidence on how curriculum implementation relates to learning outcomes remains limited, particularly in senior high school English classes. This study addresses that gap by applying the CIPP evaluation model to explore the relationships among Context, Input, Process, and Product components. Using a mixed-methods approach, data were collected from students and teachers in four senior high schools in Kabupaten Bandung through a questionnaire and semi-structured interviews. The results indicate that, among the three components, process exhibits the strongest relationship with product, followed by input and context. Qualitative findings further indicated that effective classroom practices play a central role in supporting student learning. Overall, the results suggest that the successful implementation of the Merdeka Curriculum in English classes is closely related to supportive learning environments, adequate instructional resources, and well-managed teaching–learning processes.